Number of polyps detected is a useful indicator of quality of clinical colonoscopy - Amano, Takahiro; Nishida, Tsutomu; Shimakoshi, Hiromi; Shimoda, Akiyoshi; Osugi, Naoto; Sugimoto, Aya; Takahashi, Kei; Mukai, Kaori; Nakamatsu, Dai; Matsubara, Tokuhiro; Yamamoto, Masashi; Hayashi, Shiro; Nakajima, Sachiko; Fukui, Koji; Inada, Masami (Endoscopy International Open, 2018)
Background and study aims Adenoma detection rate (ADR) is a well-known quality indicator (QI) for colonoscopy. It is, however, difficult to evaluate ADR during practice. The aim of this study was to investigate the number of endoscopically detected polyps as a QI for colonoscopy.Patients and methods This was a retrospective single-center cohort study of 5,190 consecutive patients who underwent colonoscopy from January 2015 to May 2016. Among these patients, we ultimately enrolled 1,937 patients for initial colonoscopy. We evaluated QIs including bowel preparation, cecum intubation time, withdrawal time, number of endoscopically detected polyps, ADR and advanced neoplasia detection rate (ANDR)Results The mean number of endoscopically detected polyps, ADR and ANDR were 1.5 ± 2.3 (95 % confidence interval (CI)1.4 – 1.6), 38.6 % (95 % CI 36.5-40.8), and 18.3 % (95 % CI 16.6 – 20.1), respectively. ADR and ANDR increased with the number of endoscopically detected polyps, but the correlation reached a plateau at five or more polyps. We divided the patients into three groups based on the number of polyps (1 to 2, 3 to 4, and 5 or more). Logistic regression analysis adjusted by age and sex revealed that presence of a large number of polyps was a strong predictor of advanced neoplasia (odds ratio: 3.1 [95 % CI 2.2 – 4.3] for 3 to 4 polyps and 7.9 [95 % CI 5.4 – 11.8] for 5 or more polyps when using the presence of 1 or 2 polyps as a reference).Conclusion The number of endoscopically detected polyps can predict risk of advanced neoplasia and may thus be a new QI for colonoscopy.